Space-time clusters of severe acute respiratory syndrome and COVID-19 and hierarchical urban network in the state of Mato Grosso, Brazil, 2020-2021 - Alves, Mario Ribeiro; Souza-Santos, Reinaldo; Almeida, Andréa Sobral de (Espaço para a Saúde, 2022)
Objective: to analyze the space-time distribution of COVID-19 in the state of Mato Grosso, Brazil. Methods: Weekly case records of Severe Acute Respiratory Syndrome were obtained from the Ministry of Health’s Database related to this syndrome, including data from COVID-19. Temporal and spatiotemporal analysis using scanning statistics to identify clusters of severe acute respiratory syndrome cases were performed with the software SaTScan. Results: A total of 27,093 cases was observed, with an incidence of 768.33/100,000 inhabitants. The spatial distribution considering the period of study evidenced the heterogeneity of values in the state. The highest incidence rates were observed in more populous municipalities. Conclusion: We highlight priority areas for interventions, aiming at controlling the transmission of the disease and reducing transmission risks to more remote areas of the state of Mato Grosso.